The effect of black liquor on rattan waste binderless board (BPB) produced via digestion-hot pressing (DHP) process - T., Maisarah; Ahmad, Zuraida; A., Marjan (Asian Research Publishing Network (ARPN), 2015)

(untitled)
This paper investigates the feasibility of integrating Black Liquor (BL) on a Binderless Board (BB) from rattan waste that has undergone a Digestion-Hot Pressing process (DHP). In this project, the BL was produced by means of a kraft pulping process and was characterized in terms of its viscosity, alkalinity and functional group (using FTIR). The BB was fabricated on laboratory scales by adding different compositions of BL (0% BL, 10% BL, 20% BL and 30% BL) to the rattan waste. Performance evaluation was executed to study the effect of BL on the properties of BB. The BB with 30% BL gave the highest strength values of Modulus of Rupture (MOR) and Modulus of Elasticity (MOE), while BB with 20% BL gave the highest value of internal bond (IB) strength. However, the BB with 0% BL, which performed as control, had the lowest dimensional stability properties in terms of Water Absorption (WA) and thickness swelling. Higher amounts of BL increased the properties of rattan waste BPB due to increase in lignin content and so reducing the void spaces among particles. Therefore, adding BL into BB resulted in positive effects on the properties of BBs produced.